Imaging and Treatment of Scaphoid Fractures and Their Complications - Taljanovic, Mihra S.; Karantanas, Apostolos; Griffith, James F.; DeSilva, Gregory L.; Rieke, Joshua D.; Sheppard, Joseph E. (Seminars in Musculoskeletal Radiology, 2012)
The scaphoid is the most commonly fractured carpal bone, with frequent complications that are predisposed by its anatomical location, anatomical configuration (shape and length), and vascular supply. The most common mechanism of injury is a fall onto an outstretched hand. Imaging plays a significant role in the initial evaluation and treatment of scaphoid fractures and their complications. Radiography should be the first imaging modality in the initial evaluation and follow-up of scaphoid fractures. Computed tomography with its superb spatial resolution enables better visualization and characterization of the fracture line, and the amount of displacement and angulation of the fracture fragments. Using the metal reduction artifact with computed tomography allows good follow-up of scaphoid fractures despite surgical hardware. Magnetic resonance imaging without contrast is the imaging modality of choice for depiction of radiographically occult scaphoid fracture, bone contusion, and associated soft tissue injury; contrast-enhanced imaging aids assessment of scaphoid fracture nonunion, osteonecrosis, fracture healing after bone grafting, and revitalization of the necrotic bone after bone grafting. Proper identification and classification of scaphoid fracture and its complications is necessary for appropriate treatment. This article describes the normal anatomy, mechanism of injury, and classification of stable and unstable fractures, together with the imaging and treatment algorithm of scaphoid fractures and their complications with an emphasis on magnetic resonance imaging.
Keywords: scaphoid; fracture; nonunion; osteonecrosis; radiography; MRI; CT; treatment